Strengthening Youth Entrepreneurial Spirit Through Organizational Capacity Building And E-Commerce Utilization: A Community Engagement Program In Wiradesa - Farida Rohmah; Husni Awali; Singgih Setiawan (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
This Community Service Program aims to strengthen the entrepreneurial spirit of the Wiradesa Youth Association through organizational strengthening and the use of e-commerce as a strategy to increase the independence and economic value of youth organizations. The methods used include institutional mentoring, entrepreneurship training, and provision of e-commerce platform utilization to support the formation of organization-based business units. The results of the activities show an increase in organizational capacity in governance, the entrepreneurial orientation of members, and the organization's readiness to manage business units as a source of added economic value. This program encourages the transformation of the role of youth organizations from merely implementing social activities to productive entities that contribute to improving the welfare of members and the surrounding environment. The novelty of this service lies in the integration of strengthening youth organizations with the development of e-commerce-based digital entrepreneurship as a model for sustainable youth empowerment.